Dioscin Reduces Vascular Damage in the Retina of db/db Mice by Inhibiting the VEGFA Signaling Pathway - Wang, Jun; Yang, Guang Yan; Sun, Hong Yan; Meng, Ting; Cheng, Chu Chu; Zhao, Hui Pan; Luo, Xiao Ling; Yang, Ming Ming (Frontiers in Pharmacology, 2022)
Diabetic retinopathy (DR) is one of the microvascular complications of diabetes and has a serious impact on the quality of life of patients. VEGFA is necessary in the physiological state to maintain the endothelial activity and physical properties of the blood vessels. VEGFA plays an important role in the formation of neovascularisation, so inhibition of VEGFA can degrade the structure of blood vessels and reduce neovascularization. In the present study, HERB, a high-throughput experimental and reference-oriented database of herbal medicines, was used for compound mining targeting VEGFA. The compounds most likely to interact with VEGFA were screened by molecular docking. Next, the compound was used to verify whether it could inhibit the activity of VEGF signaling pathway in vitro and neovascularization in vivo. In vitro we have identified that dioscin could inhibit the activation of VEGFA-VEGFR2 signaling pathway and cell proliferation of human retinal microvascular endothelial cells in a high glucose (HG) environment. More important dioscin intervention inhibits angiogenesis in the retina of db/db mice. In conclusion, our study indicates that dioscin inhibits the angiogenesis of DR in 𝑑𝑏/𝑑𝑏 mice and implies an important and potential application of dioscin for treatment of DR in clinics.